Selong Belanak Village in Central Lombok: A Destination Development Model - Hasan Basri; Ni Gst Nym Suci Murni; I Ketut Sutama; Raden Roro Rieta Anggraheni (Yayasan Sinergi Widya Nusantara, 2023)
Purpose : This study aims to determine the position of Selong Belanak Village in Central Lombok, Indonesia, according to the TALC (tourism area life cycle) in order to be developed as an attractive tourist destination. Research methods : The data were collected through observation, documentation, structured interviews, and focus group discussions. The analysis was carried out in a qualitative descriptive manner. Findings : The results of the study show that the development model of Selong Belanak Village as a tourist destination is carried out by involving three pillars, namely the government, Pokdarwis (or kelompok sadar wisata) which represents the local society, and business parties. Implications : The results of this study are Selong Belanak Village is currently in the involvement phase.